The Mechanism of Sediment Depositional Environment of Core Drilling of Gilimanuk Coast, Bali and Ketapang, East Java, Based on Sediment Textures - Ediar Usman (BULLETIN OF THE MARINE GEOLOGY, 2016)
The analysis result of grains frequency curve and relation between grains size to cumulative have shown medium grains at  Gilimanuk (Core drilling-1) and coarse grains at Ketapang (Core drilling-2). In general both of them are showed by pattern uniformity, which is represented by the similar of curve pattern. On the grain size of -2 phi as medium gravel with percentage between 6.47 to 35.88%, while core drilling -2 on the size of -2 phi between 6.86 to 61.11%.The average grains size of core drilling -1 are gravel about 21.3%, sand 60.2%, silt 5% and clay about 0.4% while core drilling-2 are  characterized by  44.3%, sand 26.8%, silt 24.6% and clay about 0.6%. These result shows that at location of Core drilling -1 is dominated by sand where as at location of Core drilling -2 is dominated by gravel. These situation can be interpreted that the sediment at core drilling -2 location have influenced by strong marine current which can transport the large amount of gravel size compare to the location of Core drilling-1 which is dominated by sand. Based on  the relation shape of grains size curve versus cumulative frequency shows that the sediment of Core drilling-1is interpreted as a beach sand deposits and only one sample which shows as a river sand deposits which was found at depth 0 – 3 m depth. In general, the sample of Core drilling –2 shows that the pattern of sediment tend as a beach sand deposits and only one sample  which shows the combination between coastal deposits and river deposits ( 4 – 5 m depth). From this sample, the coarse to fine grains is deposited by coastal media and fine grains material (about 10%) is deposited by river media. The sample of river deposits is found as lamination  because the only one which is created from combination between coastal and river depos its from all sample of core drilling-2.Keywords: core drilling, grain sediments, media transport, environmental deposition Hasil analisis menggunakan kurva frekuensi butiran serta hubungan antara besar butir terhadap kumulatif menunjukkan dominasi ukuran butiran sedang di daerah Gilimanuk (Bor-1) dan kasar di daerah Ketapang (Bor-2). Pada kedua daerah tersebut, secara umum memperlihatkan pola keseragaman, yang ditunjukkan oleh pola kurva yang sama. Pada ukuran butir -2 phi (kerikil sedang) pada Bor-1 berjumlah antara  6,47 – 35,88%, sedangkan pada Bor-2 pada ukuran -2 phi berjumlah antara 6,86 – 61,11%.Kandungan rata-rata butiran pada Bor-1 adalah: kerikil 21,3%, pasir 60,2%, lanau 5% dan lempung 0,4%, sedangkan Bor-2 adalah: kerikil 44,3%, pasir 26,8%, lanau 24,6% dan lempung 0,6%. Hasil ini menunjukkan bahwa pada Bor-1 didominasi oleh pasir dan pada Bor-2 didominasi oleh kerikil. Hasil ini dapat memberi gambaran bahwa pada Bor-2 berarus lebih kuat karena mampu menstranspor butiran kerikil dalam jumlah yang lebih besar dibandingkan dengan Bor-1 yang didominasi oleh pasir. Berdasarkan beberapa kurva hubungan antara besar butir vs frekuensi komulatif pada Bor-1 menunjukkan endapan pantai (beach sand), hanya satu contoh menunjukkan endapan sungai (river sand), yaitu contoh B1 (0 – 3m). Pada Bor-2, secara umum menunjukkan pola yang lebih mendekati endapan pantai (beach sand), hanya satu contoh menunjukkan kombinasi endapan pantai dan endapan sungai (river sand), yaitu contoh B2 (4 – 5 m). Pada contoh ini, butiran berukuran kasar sampai halus diendapkan oleh media pantai dan ukuran halus dengan persentase sekitar 10% merupakan endapan sungai. Contoh endapan sungai adalah pada B2 (4 – 5 m) ini merupakan endapan sisipan karena satu-satu terbentuk dari kombinasi pantai dan sungai dari seluruh contoh pada Bor-2.Kata kunci:  pemboran inti, butiran sedimen, media transport, lingkungan pengendapan